Flood Hazard Assessment Due to Changes in Land Use and Cover - Supratman, Maman; Kusuma, Muhammad S. B.; Cahyono, Muhammad; Kuntoro, Arno Adi (Civil Engineering Journal, 2024)
This study aimed to investigate the influence of land use changes on the occurrence of flood hazards in the Pondok Karya area, Jakarta, Indonesia. Landsat OLI 8 and 7 from 2002 to 2023 were analyzed with a supervised classification tool using Envi and ArcGIS to investigate land use changes over the period. Additionally, the HEC-HMS and HEC-RAS tools were utilized for hydrological and hydraulic assessments under 25 discharge return periods (Q25), using a daily rainfall dataset from 2004 to 2021. The flood hazard index was produced using statistical and GIS methodologies and was based on Neighbourhood Associations (NAs) after qualified hydraulic model performance, indicating a Nash 0.65–Nash-Sutcliffe model efficiency (NSE) value. The analysis revealed considerable alterations in land use and cover within the Pondok Karya watershed. Consequently, the percentage of urban areas surged 30%, whereas vegetative cover declined 24%. Additionally, bare land decreased 9%, and water bodies marginally increased 3%. This indicates a 10% increase in the peak flood river flow of Mampang, from approximately 90 m³/s to 100 m³/s within this period. Subsequently, the percentage of high-risk areas increased from 42.85% (six NAs) to 57.14% (eight NAs), whereas the percentage of low-risk areas decreased from 14.29% (two NAs) to 7.14% (one NAs). Moderate-risk areas also decreased from 42.85% (six NAs) to 35.71% (five NAs). The study found that despite vegetative cover exceeding 30%, the capacity of the Mampang River remained inadequate, and the risk of flooding increased with the impact of its conversion. Additionally, the soil properties and social intervention factors contributed to the performance of the inundation model. Our study underscores the need for further research to mitigate flood risks and advocate interventions such as reservoir construction or river normalization in the upper Mampang catchment area. This study is useful for both local and central governments, which act as decision-makers to reduce the risk of flooding. Doi: 10.28991/CEJ-2024-010-12-04 Full Text: PDF